Fish diseases and disorders - Woo, P. T. K. (CABI Pub, 2006)
This book, the first of three volumes, provides a review of the major diseases of fish caused by protozoan and metazoan parasites. The articles, written by researchers from around the world in biology, zoology, and parasitology, each focus on a particular phylum, including Myxozoa, Apicomplexa, Arthropoda, and Annelida